Pemanfaatan daun katuk (Sauropus androgynus) terhadap produksi telur ayam petelur di CV. Zafa Anugerah Mandiri Muara Badak - Harja Aryawan; Julinda Romauli Manullang; Surya Nur Rahmatullah (Jurnal Ilmu Peternakan Terapan, 2022)
Katuk plant is a plant with a height of 2-3.5 m and is known by the public as a vegetable plant with a high nutritional content, namely 6.4 g protein, 9.9 g carbohydrates and 233 mg calcium. This study was conducted to determine the effect of giving katuk leaves (Sauropus androgynus) on egg production of laying hens (Galus domecticus) at the age of rejection. A non-factorial experiment in a completely randomized design (CRD) with four treatments and six replications with katuk leaf flour in this study. The data obtained were analyzed using Analysis of Variance (ANOVA) and further tested using the 5% Least Significant Difference (BNT) test. The results of this study showed that giving katuk leaf flour were significantly different on egg production and Feed Egg Ratio (FER) but not significantly different on feed consumption. An average egg production of 54%, an average ration consumption of 114.2-119.9 g/head/day, and an average Feed Egg Ratio (FER) of 1.6-2.11. The treatment using 10 g of katuk leaf flour was the best treatment, namely an egg production of 89.88%, a ration consumption of 114.5 g/head/day and a Feed Egg Ratio (FER) of 1.6.